Dysfunctional attitudes, automatic thoughts and anxiety symptoms among Turkish youth: Results from a pilot study (Annals of Medical Research, 2021)
Aim: The aim of this study is investigating the relationship between symptoms of anxiety and measures of automatic thoughts and dysfunctional attitudes which were developed for depression. Material and Methods: One-hundred university students completed the Turkish version of Beck Anxiety Inventory (BAI), Automatic Thoughts Scale (ATQ), Dysfunctional Attitudes Scale (DAS) and a sociodemographic form. Data were analyzed by SPSS 24.Results: The results indicated that there was a moderate positive correlation between anxiety and automatic thoughts. Dysfunctional attitudes, specifically Perfectionism and Need for Approval showed weak positive correlation with anxiety symptoms.Conclusion: This finding shows that the cognitive content of both disorders cannot be fully separated.
Keywords: Anxiety; automatic thoughts; dysfunctional attitudes